Modeling complex habitat use for threatened species decision-making in a landscape with competing ecological and economic values - Robyn E. Shaw; Linette S. Umbrello; Chris G. Knuckey; Robert D. Bullen; Kristen K. Nilsson; Gisella Maquez Donayre; Teagan R. Johnston; Luke J. Porter; Harley R. Taylor; Lesley A. Gibson; Kym M. Ottewell (Biological Conservation, 2026)

Corrigendum to “Behavioural and faecal cortisol metabolite monitoring of harbour (Phoca vitulina) and grey seal pups (Halichoerus grypus) in rehabilitation centres” [Appl. Anim. Behav. Sci. 297 (2026) 106910] - Michal Zatrak; Kirsty J. Shaw; Matthew Geary; Richard Ilderton; Robyn A. Grant (Applied Animal Behaviour Science, 2026)

Behavioural and faecal cortisol metabolite monitoring of harbour (Phoca vitulina) and grey seal pups (Halichoerus grypus) in rehabilitation centres - Michal Zatrak; Kirsty J. Shaw; Matthew Geary; Richard Ilderton; Robyn A. Grant (Applied Animal Behaviour Science, 2026)

Regional conservation genomics: insights and opportunities from northern Australia - Teigan Cremona; Brenton von Takach; Robyn Shaw; Alexander Carey; Bridget Campbell; Skye Cameron; Renee Catullo; Caroline Chong; Saul Cowen; Danielle Edwards; Emilie Ens; Tony Griffiths; et al. (Biodiversity and Conservation, 2025)
Biodiversity conservation in northern Australia is characterised by high endemism, data deficiency, and high Indigenous land tenure and population. The Northern Australia Conservation Genomics Forum brought together experts to explore current genetic research with particular emphasis on integration of genomics within conservation practices. We discuss the regional biodiversity of northern Australia, highlighting the unique biogeographic patterns, known and unknown species diversity, and ongoing threats such as habitat degradation, altered fire regimes, invasive species, and climate change. This article synthesises key themes from the forum, including the current application of genomics in conservation, gaps and areas of need and opportunity to advance species conservation in this sparsely populated, yet iconic region of Australia. We highlight the need to expand collaborative research partnerships across land tenures with Indigenous organisations, pastoralists, government and non-government organisations, which is crucial for the effective study and conservation of the region’s biodiversity. The paper identifies the challenges and opportunities in applying genomic data to conservation strategies and applied management, including species translocations and habitat management, while acknowledging the limitations and gaps in current research and collections. The insights from this forum emphasise the advantages in using genomics to inform conservation decisions, and the need for continued research and collaboration to protect northern Australia’s unique biodiversity.

Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

Building meaningful collaboration in conservation genetics and genomics - Robyn E. Shaw; Brittany Brockett; Jennifer C. Pierson; Stephen D. Sarre; Paula Doyle; Hannah B. Cliff; Mark D. B. Eldridge; Kimberly A. Miller; Kym Ottewell; Marissa L. Parrott; Maurizio Rossetto; Paul Sunnucks; et al. (Conservation Genetics, 2024)
Genetic diversity is the foundation of biodiversity, and preserving it is therefore fundamental to conservation practice. However, global conservation efforts face significant challenges integrating genetic and genomic approaches into applied management and policy. As collaborative partnerships are increasingly recognized as key components of successful conservation efforts, we explore their role and relevance in the Australian context, by engaging with key entities from across the conservation sector, including academia, botanic gardens, herbaria, seed banks, governmental/non-governmental organisations, private industry, museums, Traditional Owners, Indigenous rangers, and zoos and aquaria. By combining perspectives from these entities with comprehensive literature review, we identified five guiding principles for conservation genetic and genomic research and explored the different elements of, and approaches to, collaboration. Our reflections suggest that there is a substantial overlap in research interests across the Australian conservation sector, and our findings show that collaboration is increasing. We discuss approaches to building collaborative partnerships, the reciprocal benefits of collaborating, and some remaining challenges associated with data generation, data collection, and cross-cultural considerations. We emphasise the need for long-term national resourcing for sample and data storage and consistency in collecting, generating and reporting genetic data. While informed by the Australian experience, our goal is to support researchers and practitioners to foster meaningful collaborations that achieve measurable management outcomes in conservation genetics and genomics, both in Australia and globally.

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Factors affecting the survival of harbor ( Phoca vitulina ) and gray seal ( Halichoerus grypus ) juveniles admitted for rehabilitation in the UK and Ireland - Michal Zatrak; Sam Brittain; Lauren Himmelreich; Susie Lovick‐Earle; Romain Pizzi; Kirsty J. Shaw; Robyn A. Grant; Matthew Geary (Marine Mammal Science, 2023)
The UK shores are home to approximately 40% of the world's population of gray seals ( Halichoerus grypus ) and 40% of Europe's harbor seals ( Phoca vitulina ). Stranded juvenile seals of both species are frequently rescued and admitted for rehabilitation. This study investigates the causes of P. vitulina and H. grypus admittance to rehabilitation centers in the UK and Ireland and identifies factors that can affect juvenile seal survival. Rehabilitation records for 1,435 P. vitulina and 2,691 H. grypu s were used from five rehabilitation centers from 1988 through 2020. The most common nonexclusive reasons for seal admission to rehabilitation centers included malnourishment (37%), injuries (37%), maternal abandonment (15%), lethargy (12%), and parasite infections (8%). A mixed effects logistic regression model showed that H. grypus had 4.55 times higher survival odds than P. vitulina and that the odds of survival to release multiplied by 1.07 for every kilogram over their age‐predicted weight. This weight‐dependent survival could be attributed to the importance of fat in thermoregulation, hydration, and buoyancy during foraging. We recommend that seal rehabilitators pay special attention to the weight of admitted juvenile seals during triage and treatment to enhance their odds of survival and consequent release to the wild.

Linking life history to landscape for threatened species conservation in a multiuse region - Robyn E. Shaw; Peter B. Spencer; Lesley A. Gibson; Judy A. Dunlop; Janine E. Kinloch; Karel Mokany; Margaret Byrne; Craig Moritz; Harriet Davie; Kenny J. Travouillon; Kym M. Ottewell (Conservation Biology, 2023)
Landscape‐scale conservation that considers metapopulation dynamics will be essential for preventing declines of species facing multiple threats to their survival. Toward this end, we developed a novel approach that combines occurrence records, spatial–environmental data, and genetic information to model habitat, connectivity, and patterns of genetic structure and link spatial attributes to underlying ecological mechanisms. Using the threatened northern quoll ( Dasyurus hallucatus ) as a case study, we applied this approach to address the need for conservation decision‐making tools that promote resilient metapopulations of this threatened species in the Pilbara, Western Australia, a multiuse landscape that is a hotspot for biodiversity and mining. Habitat and connectivity were predicted by different landscape characteristics. Whereas habitat suitability was overwhelmingly driven by terrain ruggedness, dispersal was facilitated by proximity to watercourses. Although there is limited evidence for major physical barriers in the Pilbara, areas with high silt and clay content (i.e., alluvial and hardpan plains) showed high resistance to dispersal. Climate subtlety shaped distributions and patterns of genetic turnover, suggesting the potential for local adaptation. By understanding these spatial–environmental associations and linking them to life‐history and metapopulation dynamics, we highlight opportunities to provide targeted species management. To support this, we have created habitat, connectivity, and genetic uniqueness maps for conservation decision‐making in the region. These tools have the potential to provide a more holistic approach to conservation in multiuse landscapes globally.

The impact of mating systems and dispersal on fine‐scale genetic structure at maternally, paternally and biparentally inherited markers - Robyn E. Shaw; Sam C. Banks; Rod Peakall (Molecular Ecology, 2018)
For decades, studies have focused on how dispersal and mating systems influence genetic structure across populations or social groups. However, we still lack a thorough understanding of how these processes and their interaction shape spatial genetic patterns over a finer scale (tens—hundreds of metres). Using uniparentally inherited markers may help answer these questions, yet their potential has not been fully explored. Here, we use individual‐level simulations to investigate the effects of dispersal and mating system on fine‐scale genetic structure at autosomal, mitochondrial and Y chromosome markers. Using genetic spatial autocorrelation analysis, we found that dispersal was the major driver of fine‐scale genetic structure across maternally, paternally and biparentally inherited markers. However, when dispersal was restricted (mean distance = 100 m), variation in mating behaviour created strong differences in the comparative level of structure detected at maternally and paternally inherited markers. Promiscuity reduced spatial genetic structure at Y chromosome loci (relative to monogamy), whereas structure increased under polygyny. In contrast, mitochondrial and autosomal markers were robust to differences in the specific mating system, although genetic structure increased across all markers when reproductive success was skewed towards fewer individuals. Comparing males and females at Y chromosome vs. mitochondrial markers, respectively, revealed that some mating systems can generate similar patterns to those expected under sex‐biased dispersal. This demonstrates the need for caution when inferring ecological and behavioural processes from genetic results. Comparing patterns between the sexes, across a range of marker types, may help us tease apart the processes shaping fine‐scale genetic structure.

The role of relatedness in mate choice by an arboreal marsupial in the presence of fine-scale genetic structure - Michaela D. J. Blyton; Robyn E. Shaw; Rod Peakall; David B. Lindenmayer; Sam C. Banks (Behavioral Ecology and Sociobiology, 2016)

Fine‐scale refuges can buffer demographic and genetic processes against short‐term climatic variation and disturbance: a 22‐year case study of an arboreal marsupial - Sam C. Banks; Thibault Lorin; Robyn E. Shaw; Lachlan McBurney; David Blair; Michaela D.J. Blyton; Annabel L. Smith; Jennifer C. Pierson; David B. Lindenmayer (Molecular Ecology, 2015)
Ecological disturbance and climate are key drivers of temporal dynamics in the demography and genetic diversity of natural populations. Microscale refuges are known to buffer species’ persistence against environmental change, but the effects of such refuges on demographic and genetic patterns in response to short‐term environmental variation are poorly understood. We quantified demographic and genetic responses of mountain brushtail possums ( Trichosurus cunninghami ) to rainfall variability (1992–2013) and to a major wildfire. We hypothesized that there would be underlying differences in demographic and genetic processes between an unburnt mesic refuge and a topographically exposed zone that was burnt in 2009. Fire caused a 2‐year decrease in survival in the burnt zone, but the population grew after the fire due to immigration, leading to increased expected heterozygosity. We documented a fire‐related behavioural shift, where the rate of movement by individuals in the unburnt refuge to the burnt zone decreased after fire. Irrespective of the fire, there were long‐term differences in demographic and genetic parameters between the mesic/unburnt refuge and the nonmesic/burnt zone. Survival was high and unaffected by rainfall in the refuge, but lower and rainfall‐dependent in the nonmesic zone. Net movement of individuals was directional, from the mesic refuge to the nonmesic zone, suggesting fine‐scale source–sink dynamics. There were higher expected heterozygosity ( H E ) and temporal genetic stability in the refuge, but lower H E and marked temporal genetic structure in the exposed habitat, consistent with reduced generational overlap caused by elevated mortality and immigration. Thus, fine‐scale refuges can mediate the short‐term demographic and genetic effects of climate and ecological disturbance.

Genetic analyses of bolting in bulb onion (Allium cepa L.) - Samantha Baldwin; Roopashree Revanna; Meeghan Pither-Joyce; Martin Shaw; Kathryn Wright; Susan Thomson; Leire Moya; Robyn Lee; Richard Macknight; John McCallum (Theoretical and Applied Genetics, 2014)

Development of a powerful microsatellite marker panel for Trichosurus cunninghami - Michaela D. J. Blyton; Robyn Shaw; Sam C. Banks (Conservation Genetics Resources, 2014)